Hands-on RESTful web API design patterns and best practices : design, develop, and deploy highly adaptable, scalable, and secure RESTful web APIs - Subramanian, Harihara; Raj, Pethuru (Packt Publishing, 2019)
REST architecture (style) is a pivot of distributed systems, simplify data integration amongst modern and legacy applications leverages through the RESTful paradigm. This book is fully loaded with many RESTful API patterns, samples, hands-on implementations and also discuss the capabilities of many REST API frameworks for Java, Scala, Python and Go.